Coexistence of Spinal Intramedullary Tuberculoma and Multiple Intracranial Tuberculomas - Lee, Dong-Yoon (Korean J Spine, 2015)
Spinal intramedullary tuberculoma remains a very rare entity of central nervous system tuberculosis. This is the same with the coexistence of spinal intramedullary and intracranial tuberculomas that remains extremely rare with less than 20 cases reported at present. Authors describe this uncommon case by analyzing a 65-year-old female patient who had past history of kidney transplantation due to stage 5 chronic kidney disease and pulmonary tuberculosis on medication. The patient experiences progressive paraplegia and numbness on both lower extremities. Magnetic resonance imaging demonstrated an intramedullary mass at T9-10 level and multiple intracranial enhancing nodules. Microsurgical resection of spinal intramedullary mass was performed and the lesion was histopathologically confirmed as Mycobacterium tuberculosis. Efficient diagnosis and management of this rare disease are reviewed along with previously reported cases.